White Matter Injury after Intracerebral Hemorrhage: Pathophysiology and Therapeutic Strategies - Tao, Chuanyuan; Hu, Xin; Li, Hao; You, Chao (Frontiers in Human Neuroscience, 2017)
Intracerebral hemorrhage(ICH) accounts for 10-30% of all types of stroke. Bleeding within the brain parenchyma causes gray matter (GM) destruction as well as proximal or distal white matter (WM) injury (WMI) due to complex pathophysiological mechanisms. Because WM has a distinct cellular architecture, blood supply pattern and corresponding function, and its response to stroke may vary from that of GM, a better understanding of the characteristics of WMI following ICH is essential and may shed new light on treatment options. Current evidence using histological, radiological and chemical biomarkers clearly confirms the spatio-temporal distribution of WMI post- ICH. Although certain types of pathological damage such as inflammatory, oxidative and neuro-excitotoxic injury to WM have been identified, the exact molecular mechanisms remain unclear. In this review, we briefly describe the constitution and physiological function of brain WM, summarize evidence regarding WMI, and focus on the underlying pathophysiological mechanisms and therapeutic strategies.